Предмет: Алгебра,
автор: leonmx
решите уравнение
4x²-24=0
(x-2)(x+2)-x(x-3)=0
Ответы
Автор ответа:
0
4х^2-24=0
4х^2=24
х^2=24/4
х= √6
(х-2)(х+2)-х (х-3)=0
х^2+2х-2х-4-х^2+3х=0
3х=4
х=4/3
4х^2=24
х^2=24/4
х= √6
(х-2)(х+2)-х (х-3)=0
х^2+2х-2х-4-х^2+3х=0
3х=4
х=4/3
Автор ответа:
0
Ответ:
1)4x^2-24=0 |/2
2x^2-12=0 |/2
x^2-6=0
x^2=6
x=+-_/6
2)(x-2)(x+2)-x(x-3)=0
x^2-4-x^2+3x=0
-4+3x=0
3x=4
x=4/3
x=1*1/3
1)4x^2-24=0 |/2
2x^2-12=0 |/2
x^2-6=0
x^2=6
x=+-_/6
2)(x-2)(x+2)-x(x-3)=0
x^2-4-x^2+3x=0
-4+3x=0
3x=4
x=4/3
x=1*1/3
Похожие вопросы
Предмет: Информатика,
автор: sganneo2
Предмет: Математика,
автор: sadrudinovmagomed9
Предмет: Геометрия,
автор: Vlados7890
Предмет: Математика,
автор: ihibstor
Предмет: Математика,
автор: ebuzdes